The Implementation of Flipped Classroom Approach in an Academic English Course - Thinh, Nguyen Thi (VNU Journal of Foreign Studies; Vol 37 No 3, 2021)
Since flipped classroom (FC) approach was first implemented over a decade ago, it has been gathering great momentum with more and more research conducted in different fields over the past years. As an attempt to better understand this promising new model, this study aimed to apply it in an academic English language course and examine its effects on student’s perception and the quality of their assignment together with the instructor’s self-reflection. The participants were 21 sophomores attending an academic English course (integrated reading and writing section) at a state university in Hanoi, Vietnam. Combining both quantitative data from survey and qualitative data from feedback forms together with the instructor’s reflection and analysis of students’ work, findings of the study indicated positive perception towards flipping learning mode from both the students and instructor’s perspective and the analysis of the submitted end-of-course assignments showed a good mastery of essay genres, argument development and text selection. However, synthesizing skill as well as the use of APA in-text citations and references needed more guidance and required more practice. The study also pointed out some limitations and recommendations which further research should take into consideration for a better implementation of a flipped classroom.